Analisis Yuridis Upah Pekerja dalam Proses Pemutusan Hubungan Kerja berdasarkan Putusan Hakim - Junan Gunawan Panjaitan (Journal of Law and Policy Transformation, 2019)
Expanding understanding of working relationships between labors and employers become involving government as the third parties. In industrial relations, the elements involved should play their roles and functions properly, creating harmonious relationships that can stimulate economic growth. So the aim of this research is to know the interpretation of Law No. 13 Year 2003 concerning Manpower against the wages of workers / laborers under process during termination.In this case the author conducted this study using a normative juridical approach. The judge's decision that provides 6 (six) months of process wages or more is based on the theory of justice law, namely the thought that the decision-making process base on both parties justice consideration. Judges' decisions that provide zero process wages in accordance with theory progressive law which consider the benefit of both parties labors and employers and development of one area specific and national generally.